(untitled) (Journal of Nepal Geological Society, 2025)
The knowledge of fragmentation with explosives has allowed a critical look at the theoretical principles and rules of Langefors. The blasting operations at the Ekona quarry are usually accompanied by the production of oversized blocks, which require secondary operations that increase the cost of production. Therefore, a methodology related to the design of a blast plan allowing good fragmentation of the massif is needed. Petrographic observations made it possible to identify and generally describe the massif, which is a prismatic basalt. Structurally, the families of major fracture directions are grouped into two main types, namely, family A: N0-N30, and family B: N30-N60. The analysis of the results obtained for a given step made it possible to detect the influence of several parameters (e.g., the mesh size and inclination of the holes) on the fragmentation results. For a good distribution of the explosive charges and for a regular drilling mesh of 3 × 2.5 m2 over a depth of 10 m, we obtain better results than those of the quarry with a gain in specific consumption of explosives of 35%. As a result, the adopted Langefors optimization method has shown that the cost of explosives can reach approximately 30% for 10 m holes and 41% for 12 m holes.